Rectal, telemetry pill and tympanic membrane thermometry during exercise heat stress - Easton, C.; Fudge, B. W.; Pitsiladis, Y. P. (Journal of Thermal Biology, 2007)
We compared the accuracy of an ingestible telemetry pill method of core temperature (Tc) measurement and an infrared tympanic membrane thermometer to values from a rectal thermistor during exercise-induced heat stress. Ten well-trained subjects completed four exercise trials consisting of 40 min constant-load exercise at 63% of maximum work rate followed by a 16.1 km time trial at 30 °C and 70% relative humidity. Temperature at rest was not different between the three methods of Tc measurement (Tre: 37.2±0.3 °C; Tp: 37.2±0.2 °C; Tty: 37.1±0.3 °C; P=0.40). Temperature rose continuously during the exercise period (?Tre: 2.2±0.5 °C; ?Tp: 2.2±0.5 °C; ?Tty: 1.9±0.5 ±°C and there were no differences between Tre and Tp measurements at any time throughout exercise (P=0.32). While there were no differences between Tre and Tty after 10 min (P=0.11) and 20 min (P=0.06) of exercise, Tty was lower than Tre after 30 min of exercise (P<0.01) and remained significantly lower throughout the remainder of the exercise period. These results demonstrate that the telemetry pill system provides a valid measurement of trunk temperature during rest and exercise-induced thermal strain. Tty was significantly lower than Tre when temperature exceeded 37.5 °C. However, whether these differences are due to selective brain cooling or imperfections in the tympanic membrane thermometer methodology remains to be determined.